NATIONALISM IN KOREA IN THE LATE 19th AND EARLY 20th CENTURIES - Thu, Nguyen Le; Ngoc, Tran Tung (VNU Journal of Foreign Studies; Vol 36 No 2, 2020)
Nationalism is, among ideologies, an ideology penetrating into not only Korea but also East Asian nations in the modern period at the end of 19 th century and in the early 20 th century. Nationalism is also a very influencial ideological movement throughout the historical and cultural course of Korea. The paper aims to review the acceptance process of and views on nationalism under oustanding Korean intellectuals and scholars’ eyes in the early 20 th century. Additionally, the study identifies the characteristics of nationalist ideology and its effects on social life in terms of patriotic struggle, trends toward research and national education as well as artistic and creative literature aspects.